Rapid self-sustaining consolidation of titanium silicide (Ti5Si3) via transient liquid phase reaction induced by an electric discharge. (April 2019) - Lee, W.H.; Cheon, Y.W.; Yoon, Y.H.; Jeong, C.H.; Van Tyne, C.J.; Lee, H.G.
Abstract: The fabrication of Ti5 Si3 in the form of a solid product directly from an elemental 37.5 at.% Si and 62.5 at.% Ti powder mixture was carried out by two different powder metallurgy routes. The first was by uniaxial pressing of the reactant powder mixture with sequent vacuum-sintering, and the second was by electric discharge sintering (EDS) of reactant powder mixture. The pressing process combined with vacuum-sintering produced a porous compact with multi phases of titanium silicide such as Ti5 Si3, Ti5 Si4, TiSi2, and TiSi, including elemental Ti, which indicated an incomplete phase transformation into Ti5 Si3 . On the other hand, the EDS induced the phase transformation mostly into Ti5 Si3 with a small amount of Ti5 Si4 in <180 μsec, which had a sequent consolidation into a solid compact with an average crystallite size of 30.4 nm and a lattice parameter of a = 7.42 Å and c = 4.91 Å. The significantly higher hardness value of the EDS compacts can be the result of the high density and the fine microstructure stemming from the homogeneous dissolution of the elements and the constrained grain growth. The formation of Ti5 Si3 solid compact from the stoichiometric Ti and Si powder mixture by EDS can be dominated by the solid to liquid phase transformation mechanism. Abstract : Graphical abstractUnlabelled Image Highlights: EDS induced the phase transformation mostly into Ti5 Si3 in <180 μsec. Significantly high hardness was a result of high density and fine microstructure with a constrained grain growth. The formation of Ti5 Si3 solid compact was dominated by the solid to liquid phase transformation mechanism. EDS process can produce the high purity intermetallic solid products with a low energy consumption.